Restoration of digestive continuity. Simple anastomoses. - Cendán Alfonzo, Juan E; Gilardoni, Federico (Cirugía del Uruguay, 1974)
The experience gathered with the various techniques applied has shown that to obtain good results, it is necessary that the restoration of esophagointestinal continuity is carried out under certain conditions.